Non-response of Epstein-Barr virus-associated breast cancer after primary chemotherapy: report of two cases - Gutjahr, Ewgenija; Fremd, Carlo; Arnscheidt, Johanna; Penzel, Roland; Wacker, Jürgen; Sinn, Peter (Pathogens, 2023)
Based on epidemiological evidence and molecular findings, a possible association of Epstein-Barr virus (EBV) with the carcinogenesis of breast cancer has been described. However, the frequency of EBV in breast cancer and the role of EBV regarding tumor progression or therapeutic results is largely unexplored. Here, we report on two cases of advanced, lymph node-positive invasive breast cancer of no special type (NST), histologically showing no clinical or histological evidence of tumor regression as an equivalent of a lack of response to primary systemic therapy. Both tumors were considered to be EBV-associated due to their positivity in EBV-encoded RNA (EBER) in situ hybridization (ISH) and their immunoreactivity against EBV Epstein-Barr nuclear antigen 1 (EBNA1). We hypothesize that the unusual non-response to chemotherapy in these cases of breast cancer classified as triple-negative and HER2-positive may be linked to the EBV co-infection of tumor cells. Therefore, EBV tumor testing should be considered in patients with breast cancer presenting with resistance to chemotherapy. This hypothesis may provide a new aspect in the context of EBV-associated mechanisms of tumor progression.
Gesehen am 01.03.2024